It Takes All of Us: How the Cystic Fibrosis Foundation Is Supporting States in Advancing Cystic Fibrosis Newborn Screening - Mary Dwight; Albert Faro (International Journal of Neonatal Screening, 2025)
The publication of Cystic Fibrosis Newborn Screening: A Systematic Review-Driven Consensus Guideline from the United States Cystic Fibrosis Foundation (CFF) presents the challenge of implementation. CFF is prepared to partner with stakeholders to enhance newborn screening (NBS) practices. Through funding provided to the Center for Public Health Innovation (CPHI), the CFF has helped establish two genetic testing resource centers to help states implement CFTR sequencing within the NBS algorithm. CPHI, with CFF funding, is facilitating quality improvement collaboratives that unite CF clinicians and NBS staff nationwide to share best practices in laboratory methods, communication, and education. CFF continues to fund the Screening Improvement Program Award for Optimizing the Diagnosis of Infants and has developed a toolkit to help CF care teams collaborate with NBS programs on guideline implementation. Together, these initiatives aim to support states and CF providers in adapting their algorithms and processes. By identifying current best practices to improve timeliness, sensitivity, and equity in CF NBS, CFF seeks to promote better outcomes for all individuals with CF. Recognizing the competing demands on state public health departments, CFF is committed to partnering with stakeholders to ensure meaningful improvements in CF NBS.